Eliminating Challenges and Promoting Autonomy: The Power of the English Club for High School Students - Mustofa, Anggi Yusuf; Indah, Rohmani Nur (Institut Agama Islam Negeri Madura, 2023)
Abstract: The English club is one of the available platforms to learn English that has a lot of potential sides for EFL students. This study aimed to examine the role of the English club for EFL students related to how this program could help the students cope with their challenges and promote autonomy in learning English. This research employed a qualitative descriptive approach to examine and comprehend the level of challenges and participants' standpoints toward the English club. The results revealed participants' positive perception toward the English club alleviates students' challenges while learning English. This program provides a relaxed learning model outside the formal class, which boosts their confidence, engagement, and language ability. When joining an English club, students engage in several activities which promote them to be critical thinkers and autonomous learners in their language acquisition process. As an implication, the English club provides a lot of potential to benefit students in overcoming their challenges in learning English through its activities. The supportive and collaborative environment provided by the English club fostered a sense of less stress and encouraged students to take charge of their language learning process.